Parental alcohol abuse and eating behaviors in adolescents - Cur, Anna; Szymona, Kinga; Domański, Marek; Opolska, Aneta; Jojczuk, Mariusz (Polish Journal of Public Health, 2016)
Introduction. Parental alcohol abuse hinders a child’s development, which means that these children are more exposed to mental health problems.Aim. The aim of this study was to analyze the link between the intensity of eating disorders in youngsters and family alcoholism.Material and methods. The study was conducted among adolescents in the Lubelskie province. 1766 students, aged 12 to 22 were participants in the study. The authors used a method called Eating Disorder Inventory, as well as a self-designed questionnaire that included assessing the characteristics of every family.Results. The findings of this study show that increased symptoms of eating disorders in children and teenagers correlates with alcohol dependency in the family. Adolescent children of alcoholics have higher levels of conflict identifying feelings and emotions (hunger, security) correctly. They were more likely to deem their actions as ineffective, as well as they were more frequently prone to binge eating than individuals who were not affected by drinking parents.Conclusions. There is a need for some future work and preventive measures to be taken in families affected by problem drinking.